Low temperature resistivity anomalies in Pr-based nano-manganites (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The low-temperature electronic transport behavior of under doped polycrystalline Pr0.8Sr0.2MnO3 (PSMO) manganite nanoparticles (down to 40 nm), have been investigated in the presence of applied external magnetic fields (Hext) and a distinct resistivity minimum (Ïmin) is observed below 50 K for each PSMO sample. It has been found that both depth of Ïmin, and temperature of resistivity minima ( ï²min T ) values enhance with increase of Hext. Considering various possibilities like Coulomb blockade theory, electron-electron interaction, phase separation, Kondo mechanism, we conclude that occurrence of low temperature resistivity anomalies (